IFN-γ stimulates autophagy-mediated clearance of Burkholderia cenocepacia in human cystic fibrosis macrophages. - Kaivon Assani; Mia F Tazi; Amal O Amer; Benjamin T Kopp (PLoS ONE)
Burkholderia cenocepacia is a virulent pathogen that causes significant morbidity and mortality in patients with cystic fibrosis (CF), survives intracellularly in macrophages, and uniquely causes systemic infections in CF. Autophagy is a physiologic process that involves engulfing non-functional organelles and proteins and delivering them for lysosomal degradation, but also plays a role in eliminating intracellular pathogens, including B. cenocepacia. Autophagy is defective in CF but can be stimulated in murine CF models leading to increased clearance of B. cenocepacia, but little is known about autophagy stimulation in human CF macrophages. IFN-γ activates macrophages and increases antigen presentation while also inducing autophagy in macrophages. We therefore, hypothesized that treatment with IFN-γ would increase autophagy and macrophage activation in patients with CF. Peripheral blood monocyte derived macrophages (MDMs) were obtained from CF and non-CF donors and subsequently infected with B. cenocepacia. Basal serum levels of IFN-γ were similar between CF and non-CF patients, however after B. cenocepacia infection there is deficient IFN-γ production in CF MDMs. IFN-γ treated CF MDMs demonstrate increased co-localization with the autophagy molecule p62, increased autophagosome formation, and increased trafficking to lysosomes compared to untreated CF MDMs. Electron microscopy confirmed IFN-γ promotes double membrane vacuole formation around bacteria in CF MDMs, while only single membrane vacuoles form in untreated CF cells. Bacterial burden is significantly reduced in autophagy stimulated CF MDMs, comparable to non-CF levels. IL-1β production is decreased in CF MDMs after IFN-γ treatment. Together, these results demonstrate that IFN-γ promotes autophagy-mediated clearance of B. cenocepacia in human CF macrophages.